Researching MOOC: the hypes of theory, the selection of methodology and the struggle of practice - Ab. Jalil, Habibah; Bakar, Norasiken; Jano, Zanariah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
In the effort to expand and improve access to the Malaysian Public Institutions of Higher Education, four pilot courses have been chosen whereby 30% of the overall content was developed in the form of Massive Open Online Course (MOOC). This initiative is a collaborative effort among various parties at all levels to improve the quality of teaching and learning in these institutions. This paper aimed to evaluate the effectiveness of the deployment of the pilot MOOC. Taking advantage of the research experience, this paper analyzes three main concerns pertaining to studies on the Massive Open Online Course (MOOC); understanding the context; appropriate methodology and challenges; and turning research findings into practice.